Clinical practice guidelines for acute kidney injury: a systematic review of the methodological quality - Ruizhe Li; Lanxia Wu; Xinhui Wu; Qingyang Fu; Mingyu Xu; Xu Zhai; Junfei Chen (Frontiers in Medicine, 2025)
ObjectiveHospitalized patients, particularly those in the ICU, face a significant risk of acute kidney injury (AKI). Clinical practice guidelines (CPGs) that outline diagnostic and therapeutic strategies for AKI can be valuable tools for healthcare professionals, but their effectiveness hinges on their quality. The research aims to conduct a systematic review focusing on the methodological and reporting quality of CPGs addressing acute kidney injury.DesignA systematic review of CPGs for the management of acute kidney injury in adult patients.Data resourcesPubMed and other related databases were systematically searched from January 2012 to January 2023 to collect clinical guidelines and expert consensus on acute kidney injury. After summarizing the basic information, the methodological and reporting quality of the included guidelines or expert consensus was evaluated using the AGREE II and RIGHT tools.ResultsA total of 8 CPGs from 6 countries and regions were included in this study, and the period was 2012–2023. In terms of methodological quality, 1 guideline was a level strongly recommended, and 6 were level B, generally recommended guidelines. While the evaluated guidelines demonstrated moderate overall reporting completeness, critical deficiencies persist in contextual transparency and quality assurance protocols, necessitating prioritized remediation in future iterations.ConclusionOur appraisal identifies the 2012 KDIGO guideline as the highest-quality AKI guidance framework currently available, which has driven global standardization of diagnostic criteria and management protocols. Our analysis reveals critical gaps in the practical applicability and transparency of current clinical practice guidelines, particularly regarding implementation strategies tailored to different populations, such as aging populations. Future iterations must prioritize demographic inclusivity, with explicit recommendations addressing the diagnostic challenges and management complexities of AKI among different populations.